(3CLhHI eSGFd OYhI GdCWHGA dGHf HWdGfs - (3Ydj Hf gHI Gddg Hf Ydj Hf GdMSjf, CHh GdMSf GHf CKQOj , J HYO (B507 (3g`s; (3GHf HWdGf , GdeNJGQ Hf GdMSf Hf YHOhf, CHh GdMSf,J (B458 (3g` s
(3ChdgG (B:s
(3SCdJfi CjOc Gddg EjVGM GdeSGFd GdJi ChOYgG GdTjN CHh GdMSf Hf HWdGf QMeg Gddg ai ebGdJg GdehSheI HOYhI GdCWHGA s
(3BNQgG (B:s
(3hfMf fTGgO GdehdhOjf SGYI hdGOJge bHd Cf jZJPhG HGddHf Ch HZjQg jJHQRhf TjFkG jejd Edi GdShGO ebOGQg jSjQ hGdYQH JSejg GdYbi agPG aVdI Ci TF gh ? JeJ s
(3fSNI KGdKgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B191 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B210s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B3 s
Keywords: (3GdWHs